Integration of and visions for community pharmacy in primary health care in Denmark - Hansen, Rikke N. (Pharm Pract (Granada), 2021)
In 2014, the Danish government launched a plan for health entitled: “Healthier lives for everyone – national goals for the health of Danes within the next 10 years”. The overall objective is to prolong healthy years of life and to reduce inequality in health. In Denmark, the responsibility for health and social care is shared between the central government, the regions and the municipalities. National and local strategies seek to enhance public health through national and local initiatives initiated by different stakeholders. The Danish community pharmacies also contribute to promoting public health through distribution of and counselling on medication in the entire country and through offering several pharmacy services, six of which are fully or partly remunerated on a national level. Because of greater demands from patients, health care professionals and society and a lack of general practitioners, the Danish community pharmacies now have the opportunity to suggest several new functions and services or to extend existing services. The Danish pharmacy law changed in 2015 with the objective to maintain and develop community pharmacies and to achieve increased patient accessibility. The change in the law made it possible for every community pharmacy owner to open a maximum of seven pharmacy branches (apart from the main pharmacy) in a range of 75 km. This change also increased the competition between community pharmacies and consequently the pharmacies are now under financial pressure. On the other hand, each pharmacy may have been given an incentive to develop their specific pharmacy and become the best pharmacy for the patients. Community pharmacies are working to be seen as partners in the health care system. This role is in Denmark increasingly being supported by the government through the remunerated pharmacy services and through contract with municipalities. Concurrent with the extended tasks for the Danish community pharmacies and utilisation of their excellent competencies in medication the community pharmacies need to focus on their main tasks of supplying medicines and implementing services. This requires efficient management, an increased use of technology for distribution and communication and continuing education and training.